Looking forward: exiting unconventional monetary policy - Mewael F. Tesfaselassie (The crisis and beyond, 2009)
With interest rates in most developed countries close to zero, it is not possible for monetary policymakers to stimulate the economy by reducing interest rates. As a result the economy is unusually sensitive to the possibility of deflation, and thoughts turn to fiscal policy in order to stabilize output and prices. This paper summarizes the current academic debate on the role of fiscal policy under current conditions. In particular, this paper argues that policymakers need to be explicit about their objectives concerning spending, debt, and inflation, to avoid expectations-driven fluctuations in output and inflation.
Keywords: 330; Geldpolitik; Policy-Mix; OECD-Staaten